(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
In recent years, digital transformation has fundamentally reshaped the operations of financial institutions worldwide. For commercial banks, digital finance tools have become a crucial strategic factor in optimizing investment activities. International experience demonstrates that fintech platforms, artificial intelligence (AI)-based investment analytics, blockchain technology, and big data analytics enable banks to make investment decisions quickly and efficiently. For instance, banks in the United States and Europe use digital investment portfolios to manage risks in real time and significantly enhance investment profitability. Moreover, online platforms facilitate interactive communication with investors, promote transparency, and provide timely financial reporting.